Atenção e memória visuoespacial: efeito da atenção na recuperação de itens na memória de trabalho visual - Teobaldo, Fabiana Pires (2016)
Visual attention and visual working memory are fundamental aspects of human cognition and understands them is critical to the study of human behavior. More recent studies have investigated how visual attention can be controlled and directed to representations held in working memory through the use of spacial retrocue in visual attention tasks. This research aimed to investigate the effect of sharing of sustained attention in the maintenance process and recovery of items in visual working memory, through three experiments using retrocue paradigm. The use of retrocue can favor the search for information stored for a short period of time in the visual working memory. However, the mechanisms responsible for this favoritism are not entirely clear, especially with regard to sustained attention in the suggested item. A secondary task of visual search was inserted into part of the conditions in order to shift attention in the range of stimuli, 50ms (CB50) or 500ms (CB500) after submission of the retrocue, the array memory was composed of a four items and it was presented for simultaneous and sequential manner. The results indicated that despite the visual search have impaired the performance of the participants, the magnitude of the effect was maintained retrodica the tests with and without visual search.